Guess who [videorecording (DVD)] - Sullivan, Kevin Rodney; Mac, Bernie; Kutcher, Ashton, 1978-; Saldana, Zoë, 1978-; Scott, Judith; Williams, Hal (Sony Pictures Home Entertainment, 2005)
Percy Jones is the understandably proud father of Theresa. She is a beautiful and intelligent young woman living in New York City. When Percy learns that his daughter is seriously dating a young man, he decides to do some research, and learns that her beau is a solid businessman. Percy arranges to meet Theresa's boyfriend and is a bit taken aback when he meets Simon. Percy never guessed that his daughter was involved in an interracial relationship. When it becomes clear that Simon and Theresa's relationship is likely to be altar-bound, Percy finds himself suddenly full of misgivings about the young man.